Conflicting Historical Texts in Tariq bin Ziyad’s Life - Al-Jabali, Khaled Hassan; Eid, Adelah Qasim Shehadeh (Journal of Ecohumanism, 2024)
The study aims to examine the differences in the historical texts in the life of Tariq bin Ziyad, including the issue of the lineage of the outstanding leader Tariq bin Ziyad, who was associated with the conquest of Andalusia with his name in the year (92 AH / 711 AD). Tariq bin Ziyad is of Persian Hamadanian descent, and some of them consider him to be a Berber from the Nafza tribe, and others said that he is of Arab origin, specifically from the Sadaf tribe that inhabited Hadramawt from the country of Yemen. The historical texts differ regarding the incident of burning ships, which was only mentioned in three sources since it is not a characteristic of Muslim leaders to burn these boats, and the accounts differed on the issue of the dispute between Musa bin Nasir and his leader Tariq bin Ziyad, and Tariq’s non-compliance with his orders, and that Tariq’s campaign was seen as an adventure doomed to failure before. Perhaps the reason why Tariq bin Ziyad did not comply with the orders of his commander was that Tariq had to reap the fruits of his struggle and victory in Wadi Laka. Before the remnants of the Goths met again, and their matter worsened, Tariq crawled to the city of Shaduna, and with this the life of the leader Musa bin Nasir ended, but we do not hear about the end of the leader Tariq bin Ziyad, and we do not know what are the reasons behind the silence of historical sources about mentioning his end, and all that he entered Damascus.